If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(u + 7) + -7u = 37 Reorder the terms: 3(7 + u) + -7u = 37 (7 * 3 + u * 3) + -7u = 37 (21 + 3u) + -7u = 37 Combine like terms: 3u + -7u = -4u 21 + -4u = 37 Solving 21 + -4u = 37 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -4u = 37 + -21 Combine like terms: 21 + -21 = 0 0 + -4u = 37 + -21 -4u = 37 + -21 Combine like terms: 37 + -21 = 16 -4u = 16 Divide each side by '-4'. u = -4 Simplifying u = -4
| 5y-2x=25 | | 3+(u+7)-7u=37 | | a(3+4)=4 | | 4a(3+4)= | | (25-3x)=(3x-17) | | 13-9x=101-37 | | 25-5y=4x-9y+13 | | 15x-90=180 | | (5x+13)=(9x-31) | | 5t/3-t/2=1 | | 5-x=2.8 | | 16=6s-20 | | 2(5-y)=2x+30 | | 3x+2-4y=1x-4 | | 4x-3(x+1)=2(x-1)-16 | | 4y-x=12 | | 3y+20=5 | | 2(y-3x)=16-12x | | 11=44x-11y | | 8u+21=45 | | (X-4)=3x+2 | | 3-5x+9=25 | | f(x)=5x^2+bx+c | | f(x)=-7x^2+28x+25 | | 6x=27y-3 | | (6*6)*(4*4*4)= | | 5(X-13)-7(6-X)+29=50-3(8-X) | | a+(a-8)=44 | | %.317=164 | | x^2+6.91830971e-7x-4e-8=0 | | x^2-3x/7x | | p+(-4)=1 |